Business Intelligence Adoption Intention Among Small Start-Up Owners: Examining The Influencing Factors Of Benefits, Sacrifice, Perceived-Value, And Desire - Wong, Chi Tin (2022)
This study aims to examine the influence of benefits variables and sacrifice variables on the perceived value of adopting BI, and investigate the mediating role of perceived value on the relationship between benefits and BI adoption intention; and between sacrifices and BI adoption intention. This study also examines the influence of intangible and tangible rewards on the desire to make a good decision; examine the influence of perceived value and the desire to make a good decision on BI adoption intention, and examine the influence of perceived value on the desire to make a good decision.